2022
DOI: 10.1002/adom.202200423
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Mixed A‐Site Cation Halide Perovskite Thin‐Films and Nanocrystals for Solar Cells and Light‐Emitting Diodes

Abstract: Over the past few years, lead-halide perovskites (LHPs), both in the form of bulk thin films and colloidal nanocrystals (NCs), have revolutionized the field of optoelectronics, emerging at the forefront of next-generation optoelectronics. The power conversion efficiency (PCE) of halide perovskite solar cells has increased from 3.8% to over 25.7% over a short period of time and is very close to the theoretical limit (33.7%). At the same time, the external quantum efficiency (EQE) of perovskite LEDs has surpasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 219 publications
0
47
1
Order By: Relevance
“…124 In addition, the mixed cation strategy in perovskites would be useful for altering their band gap. 35,125,126 For instance, previous investigations have revealed that the partial replacement of the Cs + with Rb + in CsPbBr 3 NCs increased the bandgap and blue-shifted the emission, which has successfully extended the emission peak from 460 to 500 nm with narrow emission linewidths (<25 nm) (Fig. 10f ).…”
Section: Strategies To Improve the Performance Of Single-halide Perov...mentioning
confidence: 90%
“…124 In addition, the mixed cation strategy in perovskites would be useful for altering their band gap. 35,125,126 For instance, previous investigations have revealed that the partial replacement of the Cs + with Rb + in CsPbBr 3 NCs increased the bandgap and blue-shifted the emission, which has successfully extended the emission peak from 460 to 500 nm with narrow emission linewidths (<25 nm) (Fig. 10f ).…”
Section: Strategies To Improve the Performance Of Single-halide Perov...mentioning
confidence: 90%
“…These organic A-site cations have been shown to be Page 2 of 28 Journal of Materials Chemistry A highly rotationally mobile at conditions relevant to device operation. Moreover, their motions and interplay with the electronic dynamics is a point of considerable interest as researchers aim to develop a comprehensive understanding of the molecular origins of the remarkable optoelectronic properties of HOIPs [11][12][13][14][15][16] . As such, the rotational properties of the A-site cations have been extensively studied using a battery of experimental techniques, including steady-state IR 17 and millimetre wave 18 spectroscopy, calorimetry 17 , solid-state NMR [19][20][21] , neutron scattering [22][23][24] , and most recently time-resolved ultrafast spectroscopy 10,14,[25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, their motions and interplay with the electronic dynamics of their parent material is a point of considerable interest as researchers aim to develop a comprehensive understanding of the molecular origins of the remarkable optoelectronic properties of HOIPs. [11][12][13][14][15][16] As such, the rotational properties of the A-site cations have been extensively studied using a battery of experimental techniques, including steady-state IR 17 and millimetre wave 18 spectroscopy, calorimetry, 17 solid-state NMR, [19][20][21] neutron scattering, [22][23][24] and most recently time-resolved ultrafast spectroscopy. 10,14,[25][26][27] From these extensive investigations, a picture of the rotational dynamics of the A-site cation within HOIPs has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the most dominant challenges in using this method for PSC fabrication is the sensitivity of organicinorganic perovskite films to high temperatures and pressures due to the volatile components and the soft nature of perovskite films. [66][67][68][69] The lamination methods also have been used for stacking different parts of the OPV devices, including polymeric top electrodes using an adhesive, [70][71][72] the photoactive polymer layer, 73,74 or anode and cathode half stacks. 75,76 Likewise, laminated-OPVs employ similar strategies as laminated-PSCs regarding the substrate, equipment, and processes.…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the most dominant challenges in using this method for PSC fabrication is the sensitivity of organic–inorganic perovskite films to high temperatures and pressures due to the volatile components and the soft nature of perovskite films. 66–69…”
Section: Introductionmentioning
confidence: 99%